4Cs Skills in Ecology and Biodiversity Learning: A Study of Junior High School Students’ Profiles in the Digital Era - Rukmi, Pramastuti Adiar; Hayat, Muhammad Syaipul; Novita, Mega (Unnes Science Education Journal, 2025)
Post-pandemic, gadgets have become an inseparable part of student life. This gives rise to brainrot which affects students’ critical thinking and creative thinking skills. Gadgets also create an individualistic attitude, causing students to have difficulty communicating and collaborating. Seeing this challenge, students need to be equipped with Critical Thinking, Communication, Collaboration and Creativity (4Cs) skills. This research aims to determine the 4Cs profile of Pelita Nusantara Kasih Surakarta Christian Junior High School students in studying Ecology and Biodiversity. The research method used in this research is descriptive quantitative with multiple choice questions for critical thinking skills, a questionnaire for communication and collaboration skills, and essay questions for creative thinking skills. The research sample was class VII, VIII, and IX students with a total of 150 students as respondents. The sampling technique is cluster random sampling. Data collection techniques using questionnaires and tests. The results show that the critical thinking skills score is 74, the creative thinking skills score is 56, the collaboration skills score is 73, and the communication skills score is 66. The average 4Cs skills score for Pelita Nusantara Kasih Surakarta Christian Junior High School students is 67. The results of this research show that The 4Cs skills of Pelita Nusantara Kasih Surakarta Christian Junior High School students are in the medium category, but for the creative thinking skills need to be improved because they have the lowest score compared to other skills.